2016
DOI: 10.1515/sjecr-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

The Two Faces of Galectin-3: Roles in Various Pathological Conditions

Abstract: Galectin-3, a unique chimaera-type member of the lectin family, displays a wide range of activities. is versatile molecule is involved in fundamental biological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…Gal-3 can be expressed in cytoplasm, nucleus, mitochondria, and cell surface, and it can also be secreted by macrophages and monocytes and other various cell types into the extracellular matrix and circulation ( 12 , 13 ). Intracellular Gal-3 can be transported to the cell surface or even secreted outside of cells and depending on localization Gal-3 could act as positive or negative regulator of apoptosis [reviewed in ( 14 )]. We postulated that extracellular Gal-3 is most important in interaction that leads to inflammation, as shown in lipopolysaccharide induced neuroinflammation ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gal-3 can be expressed in cytoplasm, nucleus, mitochondria, and cell surface, and it can also be secreted by macrophages and monocytes and other various cell types into the extracellular matrix and circulation ( 12 , 13 ). Intracellular Gal-3 can be transported to the cell surface or even secreted outside of cells and depending on localization Gal-3 could act as positive or negative regulator of apoptosis [reviewed in ( 14 )]. We postulated that extracellular Gal-3 is most important in interaction that leads to inflammation, as shown in lipopolysaccharide induced neuroinflammation ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Binding of Gal-3 to the polygalactosyl repeats of Leishmania leads to truncation of Gal-3 by their surface major protease, gp63. The truncated Gal-3 cannot oligomerize or form stable Gal-3 association (9). Galectin-3 interacts with Trypanosoma cruzi by binding three specific proteins of the parasite.…”
Section: Role Of Galectin-3 In Inflammationmentioning
confidence: 99%
“…8,9 Galectin-3 (Gal-3) is а soluble β-galactoside binding lectine that plays an important role in the modulation of fibrosis, inflammation and immune responses. 10,11 It is a well-known biomarker for risk stratification and prognostication in heart failure (HF) patients, but the data about the role of Gal-3 in AF are sparse. Some studies have shown that high circulating Gal-3 levels correlate with the degree of atrial fibrosis 12 and predict incident AF 13,14 .…”
Section: Introductionmentioning
confidence: 99%